2017
DOI: 10.1007/s00035-017-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation of vegetative and floral traits in the alpine plant Solidago minuta: evidence for local optimum along an elevational gradient

Abstract: Alpine plants growing along wide elevational gradients experience very different abiotic and biotic conditions across elevations. As a result of genetic differentiation and/or plastic response, conspecific plants growing in high elevations, as compared to low elevations, generally have shorter stems and lower number of flowers, but larger flower size. However, most often, detailed models of elevational variations were not examined. To reveal the pattern of elevational changes in a set of fitnessrelated morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
5
8
1
Order By: Relevance
“…In the current study, we found a significant decrease in plant height of both species of Roscoea ( R. alpina and R. purpurea ) with increased elevation. Reduction of plant height in these alpine gingers with increased elevation is consistent with several previous findings reported for tree species (Körner, 1998; Cordell et al, 1998; Kronfus & Havranek, 1999; Paulsen, Weber & Korner, 2000; Kogami et al, 2001; Li, Yang & Kräuchi, 2003; Shi et al, 2006) and herbaceous species (Takahashi & Matsuki, 2017; Kiełtyk, 2018). Similarly, a decrease of leaf length of R. alpina with the increased elevation in the current study is consistent with the previous findings (Hansen-Bristow, 1986; Schoettle, 1990; Kajimoto, 1993; Kao & Chang, 2001; Kiełtyk, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we found a significant decrease in plant height of both species of Roscoea ( R. alpina and R. purpurea ) with increased elevation. Reduction of plant height in these alpine gingers with increased elevation is consistent with several previous findings reported for tree species (Körner, 1998; Cordell et al, 1998; Kronfus & Havranek, 1999; Paulsen, Weber & Korner, 2000; Kogami et al, 2001; Li, Yang & Kräuchi, 2003; Shi et al, 2006) and herbaceous species (Takahashi & Matsuki, 2017; Kiełtyk, 2018). Similarly, a decrease of leaf length of R. alpina with the increased elevation in the current study is consistent with the previous findings (Hansen-Bristow, 1986; Schoettle, 1990; Kajimoto, 1993; Kao & Chang, 2001; Kiełtyk, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Although several previous studies have documented the effects of elevational gradient on the growth, morphology and physiology of the plants, most of the studies are focused on tree species (Cordell et al, 1998; Hultine & Marshall, 2000; Li et al, 2008). Recently a few studies have been conducted to understand how the elevational gradients affect the herbaceous plants (Gonzalo-Turpin & Hazard, 2009; Scheepens, Frei & Stöcklin, 2010; Hulshof et al, 2013; Bastida, Rey & Alcántara, 2015; Takahashi & Matsuki, 2017; Kiełtyk, 2018). These studies particularly focused on the variation of a specific trait, such as vegetative trait, reproductive trait or leaf trait.…”
Section: Introductionmentioning
confidence: 99%
“…alpina with the increased elevation in the current study is consistent with the previous findings (Hansen-Bristow, 1986;Schoettle, 1990;Kajimoto, 1993;Kao & Chang, 2001;Kiełtyk, 2018).…”
Section: Variations Of Morphological Traits With Elevationsupporting
confidence: 93%
“…In the current study, we found a significant decrease in plant height of both species of Roscoea (R. alpina and R. purpurea) with increased elevation. Reduction of plant height in these alpine gingers with increased elevation is consistent with several previous findings reported for tree species (Körner, 1998;Cordell et al, 1998;Kronfus & Havranek, 1999;Paulsen, Weber & Korner, 2000;Kogami et al, 2001;Li, Yang & Kräuchi, 2003;Shi et al, 2006) and herbaceous species (Takahashi & Matsuki, 2017;Kiełtyk, 2018). Similarly, a decrease of leaf length of R.…”
Section: Variations Of Morphological Traits With Elevationsupporting
confidence: 92%
“…Our current study illustrates a similar effect of snowmelt timing but also reveals spatial structuring of the community across the gradient that contributes to productivity differences. If species are able to locally shift upward in elevation ( Lenoir et al, 2008 ; Kiełtyk, 2017 ) or seek refuge in nearby microclimates (e.g., local depressions) where snowmelt changes are less pronounced ( Opedal et al, 2015 ), productivity changes will reflect both the immediate effects of earlier snowmelt and the longer term effects of community change.…”
Section: Discussionmentioning
confidence: 99%